Requirements engineering for safety-critical systems - Martins, Luiz Eduardo G.; Gorschek, Tony (River Publishers series in software engineering., 2021)
Safety-Critical Systems (SCS) are increasingly present in people's daily activities. In the means of transport, in medical treatments, in industrial processes, in the control of air, land, maritime traffic, and many other situations, we use and depend on SCS. The requirements engineering of any system is crucial for the proper development of the same, and it becomes even more relevant for the development of SCS. Requirements Engineering is a discipline that focuses on the development of techniques, methods, processes, and tools that assist in the design of software and systems, covering the activities of elicitation, analysis, modeling and specification, validation, and management of requirements. The complete specification of system requirements establishes the basis for its architectural design. It offers a description of the functional and quality aspects that should guide the implementation and system evolution. In this book, we discuss essential elements of requirements engineering applied to SCS, such as the relationship between safety/hazard analysis and requirements specification, a balance between conservative and agile methodologies during SCS development, the role of requirements engineering in safety cases, and requirements engineering maturity model for SCS. This book provides relevant insights for professionals, students, and researchers interested in improving the quality of the SCS development process, making system requirements a solid foundation for improving the safety and security of future systems.